2013
DOI: 10.1002/2013jd020632
|View full text |Cite
|
Sign up to set email alerts
|

Estimating aerodynamic roughness over complex surface terrain

Abstract: [1] Surface roughness plays a key role in determining aerodynamic roughness length (z o ) and shear velocity, both of which are fundamental for determining wind erosion threshold and potential. While z o can be quantified from wind measurements, large proportions of wind erosion prone surfaces remain too remote for this to be a viable approach. Alternative approaches therefore seek to relate z o to morphological roughness metrics. However, dust-emitting landscapes typically consist of complex small-scale surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 90 publications
3
83
0
Order By: Relevance
“…The open-ocean estimate of z f being similar to k is most likely an overestimate in the surfzone, owing to the foam not moving. Reducing z f by ;k/3, as suggested by land relationships by Nield et al (2013), results in a C dN10 O(1.5 3 10 23 ) (Fig. 3c) similar to the observations (Fig.…”
Section: Surfzone Foam Coverage Drag Coefficient Modelsupporting
confidence: 86%
“…The open-ocean estimate of z f being similar to k is most likely an overestimate in the surfzone, owing to the foam not moving. Reducing z f by ;k/3, as suggested by land relationships by Nield et al (2013), results in a C dN10 O(1.5 3 10 23 ) (Fig. 3c) similar to the observations (Fig.…”
Section: Surfzone Foam Coverage Drag Coefficient Modelsupporting
confidence: 86%
“…Some wind tunnel studies (e.g., [60,78]) have used creative methods, such as coloured sand, for tracking erosion and deposition around roughness elements, but detailed exploration of flow field behaviour and the evolution of bedforms around plants is still required. For instance, high-resolution terrestrial laser scanning could be used to detect mm-scale changes in height around partially vegetated erodible surfaces [186], thus helping to identify erosional and depositional regions to a high level of accuracy. In terms of modelling vegetation/sediment interactions, Raupach and Lu [87] identify problems of scaling over heterogeneous surfaces, and raise questions over how sediment deposition processes in the presence of vegetation could be adequately measured.…”
Section: Potential Future Avenues For Researchmentioning
confidence: 99%
“…On the other hand, the estimations of z 0 remain relatively constant (±0.004 m) as the DEM resolution is reduced to 0.04 m. The consistency of this method despite variations in DEM resolution and obstacle thresholds and the objective approach for deriving the obstacle threshold using a 30 % obstacle density, lends confidence to this method. Furthermore, Nield et al (2013) found that measures regarding surface heights are the best predictor of aerodynamic roughness, specifically for surfaces that comprise large elements or have patches of large and small elements. Therefore, it is expected that the obstacle threshold should vary for different sites as a function of their largest elements, which is consistent with the inter-site variability and the obstacle thresholds reported in this study.…”
Section: Surface Roughness (Z 0 )mentioning
confidence: 99%